Negotiating gender, religious and professional identities. Exploring some of the challenges of non-veiled Muslim women at work - Abdul Fatah, Farhana; Schnurr, Stephanie (Yearbook of the Poznan Linguistic Meeting, 2020)
Due to the increasing Islamisation, in contemporary Malaysia, non-veiled Muslim women have become the minority in many domains of public life, including the workplace (Hochel 2013; Izharuddin 2018; Mouser 2007). As the veil is widely regarded as a signifier of a Muslim woman’s identity and her level of piety (Ruby 2006; Stirling & Shaw 2004), a woman’s decision to not wear it can result in discriminatory treatment, such as exclusion from the religious community (Othman 2006). In this paper we give these often discriminated against women a voice and describe some of the challenges that they experience at work. Our particular focus is how these non-veiling women construct their identities – as religious Muslims, “good” women, and successful professionals – in a socio-cultural context where veiling is the norm (Hochel 2013; Izharuddin 2018; Khalid and O’Connor 2011). Drawing on 20 interviews with such women and using Bucholtz and Hall’s (2005) relationality principle, we demonstrate how through their stories of personal experience these women mobilise and orient to a range of different identities – including gender, religious and professional – which are intertwined with each other in complex ways.